Effect of growth hormones on caryopses formation and plant regeneration frequency in durum wheat x maize crosses - Puja, Puja; Gill, R S; Kumar, Satish; Mahal, G S; Bains, N S (Journal of Cereal Research, 2011)
Hormonal application is one of the most critical steps for the success of wheat x maize crosses. Tiller injections of 2,4-D have become a standard practice and 100 ppm concentration was almost invariably used for bread wheat. Separate standardization was carried out for concentration and combination of auxins as post pollination tiller injection in durum wheat x maize crosses. 2,4-D + picloram @ 100 ppm each was found to be the most efficient auxin combination giving CFF of 78.21% and EFF of 20.22%.Â  Embryo rescue medium is considered to be a major factor affecting the regeneration frequency thereby, the overall number of plants. Embryo rescue medium supplemented with 500 mg/l casein hydrolysate and 2 g/l activated charcoal was found to improve regeneration to a magnitude of 76.7%.